Potential Development and Marketing of Jawa Super Chicken Eggs to Promote Sustainable of Food Security at Ngoro-Oro Village, Gunungkidul during Covid-19 Pandemic - Ardaning Nuriliani; Hendry T.S.S.G. Saragih; Bima Mahendra; Flafiani Cios Conara; Lailly Tsania; Adi Susanto (Jurnal Pengabdian kepada Masyarakat (Indonesian Journal of Community Engagement), 2022)
The Covid-19 pandemic severely affect the economic sector especially on food security and purchasing power. Based on the program in 2019 and 2020, it has been found that jawa super hen can lay up to 20- 25 eggs/hen/month with good maintenance and feeding. This study aimed to solved the food security problem in Ngoro-oro village by educating the villagers about how to market their jawa super chicken eggs as an effort to improve the economic standard of the community. The activity was carried out for 7 months included producing alternative chicken feed using black soldier fly larvae, post-harvesting management, and evaluating consumer egg preference survey using google form which spread randomly over some different communities to determine the best promotional strategy. The Ngoro-oro villagers eagerly attended both of the trainings. Some of them even succeeded in developing maggot from the black soldier fly which can be used to produce as an alternative feed for poultry. We got 126 respondents from the consumer egg preference survey. We found that around 60% respondents prefer to consume medium size egg, light to dark brown egg and around 80% respondents are interested to try consuming jawa super eggs. Most of the respondents prefer simple and easy to read label as well as carton-based packaging for the eggs. Collecting all the information together, we found that jawa super eggs may have potency to be sell in the market as medium size brown eggs supported by a good brand, packaging, and promotion strategy.